Fungi: Friend or Foe? A Mycobiome Evaluation in Children With Autism and Gastrointestinal Symptoms. Issue 3 (March 2022) - Alookaran, Jane; Liu, Yuying; Auchtung, Thomas A.; Tahanan, Amirali; Hessabi, Manouchehr; Asgarisabet, Parisa; Rahbar, Mohammad H.; Fatheree, Nicole Y.; Pearson, Deborah A.; Mansour, Rosleen; Van Arsdall, Melissa R.; Navarro, Fernando; et al.
Abstract : ABSTRACT: Gastrointestinal (GI) symptoms often affect children with autism spectrum disorders (ASD) and GI symptoms have been associated with an abnormal fecal microbiome. There is limited evidence of Candida species being more prevalent in children with ASD. We enrolled 20 children with ASD and GI symptoms (ASD + GI), 10 children with ASD but no GI symptoms (ASD − GI), and 20 from typically developing (TD) children in this pilot study. Fecal mycobiome taxa were analyzed by Internal Transcribed Spacer sequencing. GI symptoms (GI Severity Index [GSI]), behavioral symptoms (Social Responsiveness Scale -2 [SRS-2]), inflammation and fungal immunity (fecal calprotectin and serum dectin-1 [ELISA]) were evaluated. We observed no changes in the abundance of total fungal species (alpha diversity) between groups. Samples with identifiable Candida spp. were present in 4 of 19 (21%) ASD + GI, in 5 of 9 (56%) ASD − GI, and in 4 of 16 (25%) TD children (overall P  = 0.18). The presence of Candida spp. did not correlate with behavioral or GI symptoms ( P  = 0.38, P  = 0.5, respectively). Fecal calprotectin was normal in all but one child. Finally, there was no significance in serum dectin-1 levels, suggesting no increased fungal immunity in children with ASD. Our data suggest that fungi are present at normal levels in the stool of children with ASD and are not associated with gut inflammation.